Assessing the impact of the Heat in Buildings Bill on leases in the non-domestic sector - Cheetham, Alice; Angela, Irene; Buzzing, Jonny; Hadfield, Mark (LCP Delta, 2024)
This research highlights the complex lease arrangements within the non-domestic market in Scotland and the challenges to implementing the Heat in Buildings Bill proposals for tenants and owners of these buildings. It also discusses potential impacts in the wider market.
Keywords: Retrofit; Non-domestic buildings; clean heat; property market; landlords; business owners